The Current State Of Diagnosis And Management Of Patients With Pelvic Organ Distension And Mixed Urinary Incontinence (Texas Journal of Medical Science, 2025)
Urinary incontinence in women remains one of the most complex and unresolved issues in urogynecology worldwide. Its prevalence increases with age, affecting approximately 25% of women aged 30 to 60 years and more than 50% of women over 60. Despite numerous proposed treatment methods, various theories explaining the causes of this condition, and specific treatment approaches, the problem remains unresolved. This issue significantly impacts nearly all aspects of life, severely complicates professional activities, limits social interactions, and disrupts harmony in family relationships.